Strategi Internalisasi Nilai Keagamaan pada Siswa Sekolah Menengah Pertama di Masa Covid- 19 - Alfarizi, Muhammad Salman; Arrasid, Farid; Syafi’i, Imam (Belajea: Jurnal Pendidikan Islam, 2021)
Covid-19 was declared as one of the pandemic outbreaks on an international scale, with the existence of covid teaching and learning activities that were originally running in normal social conditions were hampered and transferred to the latest technological advances, using several applications and platforms that support teaching and learning activities. However, some parties consider that this transfer is an ineffective solution, especially in an effort to instill religious values in junior high school (SMP) students. This study uses a literature study research model by utilizing existing literature and contextualized with current situations and conditions. This study presents information in a descriptive qualitative narrative. This study argues that online learning is an ineffective activity. The authors propose a reverse theory and find that there are several solutions in the process of internalizing religious values in junior high school students. This can be overcome with a varied, attractive, and active learning model. In addition, the responsibility and role of the environment has a significant influence in the succession of teaching and learning activities in order to implement the cultivation of good religious values in junior high school students.